2017
DOI: 10.1002/2017gl073439
|View full text |Cite
|
Sign up to set email alerts
|

Polar cap hot patches: Enhanced density structures different from the classical patches in the ionosphere

Abstract: Based on in situ and ground‐based observations, a new type of “polar cap hot patch” has been identified that is different from the classical polar cap enhanced density structure (cold patches). Comparing with the classical polar cap patches, which are transported from the dayside sunlit region with dense and cold plasma, the polar cap hot patches are associated with particle precipitations (therefore field‐aligned currents), ion upflows, and flow shears. The hot patches may have the same order of density enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(77 citation statements)
references
References 37 publications
7
69
1
Order By: Relevance
“…Soft electron precipitation is associated with patch A (Figure f), which is suggestive of electron heating through soft electron precipitation. This also explains the upward flux in patch A. Patches near the polar cap boundary like patch A are termed polar cap hot patches, which are accompanied by strong electron precipitation, localized field‐aligned currents, and ion upflows (Zhang et al, ). For such patches the electron temperature is much higher than the ion temperature.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…Soft electron precipitation is associated with patch A (Figure f), which is suggestive of electron heating through soft electron precipitation. This also explains the upward flux in patch A. Patches near the polar cap boundary like patch A are termed polar cap hot patches, which are accompanied by strong electron precipitation, localized field‐aligned currents, and ion upflows (Zhang et al, ). For such patches the electron temperature is much higher than the ion temperature.…”
Section: Observations and Resultsmentioning
confidence: 99%
“…Recently, measurement of total electron content (TEC) has become a very popular tool due to its capability of continuous monitoring and global coverage (e.g., Foster, 1993;Foster et al, 2005;Oksavik et al, 2006;Pi et al, 1997;Prikryl et al, 2016;Thomas et al, 2013;Zhang et al, 2017;Zou et al, 2013). Recently, measurement of total electron content (TEC) has become a very popular tool due to its capability of continuous monitoring and global coverage (e.g., Foster, 1993;Foster et al, 2005;Oksavik et al, 2006;Pi et al, 1997;Prikryl et al, 2016;Thomas et al, 2013;Zhang et al, 2017;Zou et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, Zou et al () highlight the association among airglow patches, fast flow channels, and localized field‐aligned currents (FACs), while Zou et al () show the collocation of enhanced electron fluxes (both structured and diffuse) with patches and mesoscale flows. A study by Zhang et al () has found flow channels to be particularly associated with polar cap patches that have relatively high electron temperatures, also known as “hot patches.” These polar cap patches are also associated with enhanced particle precipitations, FACs, and ion upflows. Zhang et al () suggests that since hot polar cap patches can have the same order of density enhancement as classical polar cap patches, they may be produced by dayside photoionized plasma being transported into polar cap flow channels.…”
Section: Introductionmentioning
confidence: 99%
“…A study by Zhang et al () has found flow channels to be particularly associated with polar cap patches that have relatively high electron temperatures, also known as “hot patches.” These polar cap patches are also associated with enhanced particle precipitations, FACs, and ion upflows. Zhang et al () suggests that since hot polar cap patches can have the same order of density enhancement as classical polar cap patches, they may be produced by dayside photoionized plasma being transported into polar cap flow channels. Statistical results from Ma et al () indicate that hot polar cap patches have higher convection speeds and stronger FACs, while the classical polar cap patches in the central polar cap generally show lower convection speeds and weaker FACs.…”
Section: Introductionmentioning
confidence: 99%